Fatigue strength scatter characteristics of JIS SUS630 stainless steel with duplex S–N curve. (January 2016) - Mohd, Sofian; Bhuiyan, Md. Shahnewaz; Nie, Defu; Otsuka, Yuichi; Mutoh, Yoshiharu
Highlights: Scatter behavior of fatigue strength for SUS630 stainless steel was investigated. Fatigue strength scatter at 10 6 and 10 7 cycles were small and similar to each other. The scatter of fatigue strength was in the same order of tensile strength. Abstract: The scatter behavior of fatigue strength for 17-4 PH stainless steel (JIS SUS630, equivalent to ASTM-A563 Grade 630), which exhibited a duplex S–N curve, was investigated. It was found that the fatigue strength scatter of the SUS630 at 10 6 and 10 7 cycles, which were corresponding to the fatigue strengths for the surface-induced and the subsurface-inclusion-induced crack nucleation modes, respectively, were significantly small and comparable to each other. The scatter of inclusion size in the present material was small and resulted in the small scatter of fatigue strength comparable to that for the surface-induced crack nucleation mode. The variation in size of non-metallic inclusions is known as one of the main factors for the fatigue strength scatter (Murakami, 2002) [1]. It was also found that the scatter of fatigue strength was in the same order of tensile strength.